2010
DOI: 10.1063/1.3531957
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of efficiency droop in GaN-based light emitting diodes with an insertion layer between the multiple quantum wells and n-GaN layer

Abstract: We have studied the characteristics of efficiency droop in GaN-based light emitting diodes (LEDs) with different kinds of insertion layers (ILs) between the multiple quantum wells (MQWs) layer and n-GaN layer. By using low-temperature (LT) (780 °C) n-GaN as IL, the efficiency droop behavior can be alleviated from 54% in reference LED to 36% from the maximum value at low injection current to 200 mA, which is much smaller than that of 49% in LED with InGaN/GaN short-period superlattices layer. The polarization f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Additionally, highly strained InGaN/GaN green multiple quantum wells (MQWs), due to a large lattice mismatch between the high-In-content InGaN and the GaN, exhibit strong piezoelectric-field-induced quantum-confined stark effects (QCSE), resulting in a spatial separation of the wave functions of electrons and holes in the quantum well [ 15 , 16 ]. In the past few decades, much scientific effort has focused on approaches to improve the optical and electrical properties of green LEDs [ 17 , 18 , 19 ]. It was found that hexagonal V-pits having inverted pyramids with (10-11) faceted sidewalls were generally formed in InGaN/GaN MQWs [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, highly strained InGaN/GaN green multiple quantum wells (MQWs), due to a large lattice mismatch between the high-In-content InGaN and the GaN, exhibit strong piezoelectric-field-induced quantum-confined stark effects (QCSE), resulting in a spatial separation of the wave functions of electrons and holes in the quantum well [ 15 , 16 ]. In the past few decades, much scientific effort has focused on approaches to improve the optical and electrical properties of green LEDs [ 17 , 18 , 19 ]. It was found that hexagonal V-pits having inverted pyramids with (10-11) faceted sidewalls were generally formed in InGaN/GaN MQWs [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these approaches involve inserting a buffer layer between the sapphire wafer and LED active structure, like a low-temperature GaN layer [1], AlN or AlGaN layer [2], SiO 2 layer with openings for overgrowth [3], or a short period superlattice (SL) [4]. It has been demonstrated that the SL insertion layer results in increase of IQE [5,6] and smaller photoluminescence (PL) peak shift with injection [4] due to supposedly smaller defect density and lower internal electrical fields. SL was also used to improve the electroluminescence due to better hole injection and current spreading [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanisms of the efficiency droop effect have been described, including carrier delocalization, 3,4 carrier leakage, 5,6 defects, 7 junction heating, 8 and Auger recombination. [12][13][14] Recently, some researchers have designed some structures of staggered QWs, [15][16][17] InGaN-delta-AlGaN or InN QWs, 18,19 strain-compensated QWs, 20,21 and graded-composition barriers, 22 to improve the optical properties of nitridebased LEDs. 11 These effects limit the use of LEDs in various applications where high-current and high-temperature operations are required.…”
Section: Introductionmentioning
confidence: 99%